Faktor Risiko Low Back Pain Pada Mahasiswa Jurusan Ortotik Prostetik Politeknik Kesehatan Surakarta - Martina Wulandari; Dwi Setyawan; Alfan Zubaidi (Jurnal Keterapian Fisik, 2017)
Abstract : Risk factors, Low Back Pain, Prosthetics and Orthotics Students of Health Polytechnic of Surakarta. Low Back Pain (LBP) or lower back pain is a common health problem that found in many people, not only in older people but also in younger nowadays. Low Back Pain associated with many kind of conditions and also risk factors. The etiology of LBP is widely accepted to be multi-factorial. The objectives of this study were to determine the risk factors causing LBP on Prosthetics and Orthotics students of Health Polytechnic of Surakarta. The study is cross sectional design used a questionnaire instrument to all Prosthetics and Orthotics students. Data analysis was performed by Chi square. The results showed that the prevalence of LBP after being Prosthetics and Orthotics students of Health Polytechnic of Surakarta is 32,2%. Risk factors associated with Low Back Pain were exercise (p value 0,033), daily time spend standing (p value 0,046), lifting (p value 0,027) and perceived stress (p value 0,008). Gender, body mass index and daily time spend sitting were not associate with Low Back Pain.